The Analysis of the Determinants of Fertility in Thailand - Bhuvapanich, Sasipen (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2025)
Thailand’s total fertility rate has continuously declined over the past decades due to population policies aimed at reducing the population growth rate, along with social and economic developments that have shifted attitudes and individual behaviors toward childbearing. Below-replacement fertility levels and an increase in the median age of the population have led to changes in the country’s population size and structure. This study aims to investigate the relationship between socioeconomic factor-namely female unemployment, male unemployment, and urbanization-and the fertility rate in Thailand. The study uses the Autoregressive Distributed Lag model on time series data covering the period from 1991 to 2022. The results show that female unemployment, male unemployment, and urbanization are factors that affect the fertility rate. Female unemployment has a positive effect on motherhood transitions because unemployment lowers the opportunity cost of childbearing, potentially increasing desired fertility. Among men, the unemployment–fertility relationship is mainly negative due to income effects. Urbanization is linked to a long-term fertility decline.